(untitled) - Dershowitz, Alan M (Hoboken, N.J, 2007)
"This is an engaging refutation of an insidious form of 'political correctness' of the right-the nonsensical idea that our country was founded on Christian principles. Anyone, left or right, who admires the foundations of American democracy will enjoy this spirited reminder of the Founding Fathers' true genius."
Keywords: Christianity and politics,Thiên chúa giáo và chính trị; History,Lịch sử; 18th century,Thế kỉ 18; United States,Hoa Kì